2017
DOI: 10.12691/ijpdea-5-1-6
|View full text |Cite
|
Sign up to set email alerts
|

On Another Type of Transform Called Rangaig Transform

Abstract: A new Integral Transform was introduced in this paper. Fundamental properties of this transform were derived and presented such as the convolution identity, and step Heaviside function. It is proven and tested to solve some basic linear-differential equations and had succesfully solved the Abel's Generalized equation and derived the Volterra Integral Equation of the second kind by means of Initial Value Problem. The Natural Logarithm (e.g log ln e xx  ) has been established and defined by means of modifying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Accordingly, it can be said that the algorithm chosen through this combination is powerful and effective in its use in solving nonlinear partial differential equations and ordinary differential equation. Based on the paper [27], the author demonstrated that the Rangaig transform has a clearer and deeper connection to the Laplace transform. However, there are cases that the Laplace transform cannot solve the differential equations with the variable coefficients as 1 t , but can be solved by applying the Rangaig transform (see the example 4.3 and the example 4.4 of [27]).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accordingly, it can be said that the algorithm chosen through this combination is powerful and effective in its use in solving nonlinear partial differential equations and ordinary differential equation. Based on the paper [27], the author demonstrated that the Rangaig transform has a clearer and deeper connection to the Laplace transform. However, there are cases that the Laplace transform cannot solve the differential equations with the variable coefficients as 1 t , but can be solved by applying the Rangaig transform (see the example 4.3 and the example 4.4 of [27]).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the paper [27], the author demonstrated that the Rangaig transform has a clearer and deeper connection to the Laplace transform. However, there are cases that the Laplace transform cannot solve the differential equations with the variable coefficients as 1 t , but can be solved by applying the Rangaig transform (see the example 4.3 and the example 4.4 of [27]). Therefore, the Rangaig transform can be used as an effective tool in solving integro-differential equations and is also effective when combining it with other methods to solve the linear and nonlinear in integer order or fractional order with variable coefficients of the form t n where n negative.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations